KEEPING OUR ENVIRONMENT HEALTHY TOGETHER: SUSTAINABLE WASTE MANAGEMENT POLICIES - Melyana R Pugu; Teguh Aprianto; Era Purike; Mohd. Fauzi Hussin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Effective and sustainable waste management is one of the most pressing environmental challenges of the modern era. Maintaining environmental health is not only essential for human health but also essential in ensuring the sustainability of natural resources. The research methods carried out on this study are literature by searching for references in accordance with the context of the research. Research findings show that global and local policies that integrate environmentally friendly technologies and innovative strategies in waste management. The use of the Internet of Things (IoT), robotics, and thermal waste processing techniques such as pyrolysis and gasification in forming efficient waste management systems. Implementation of advanced technology and community education play a vital role in improving the efficiency of waste management. The conclusions of this study show that sustainable waste management policies not only reduce the burden on the environment but also strengthen health infrastructure against the impact of climate change.